Burden of gallbladder cancer in Central and South America. (September 2016) - Izarzugaza, M.Isabel; Fernández, Leticia; Forman, David; Sierra, Mónica S.
Highlights: Gallbladder cancer rates in Central and South America varied by country and sex. Gallbladder cancer rates were the highest in countries located in the Andean region. The most frequent anatomic subsite diagnosed in Central and South America was gallbladder. The large proportion of unspecified cases highlights the need to improve cancer registration. Variations in rates reflect differences in data quality, coverage and healthcare access. Abstract: Rationale and objective: Gallbladder carcinoma (GBC) is a rare neoplasm yet it is the most common malignancy of the biliary tract and its prognosis is poor. Incidence of GBC is high in some areas of Central and South America and the Caribbean. We described the current burden of GBC in Central and South America (CSA). Methods: We obtained GBC incidence data from 48 population-based cancer registries in 13 countries in CSA, and national level cancer death data from the WHO mortality data base for 18 countries. We estimated World population age-standardized incidence and mortality rates per 100, 000 persons-years, including distribution and incidence rates by anatomic subsite. Results: GBC rates were the highest in countries located in the Andean region. In 2003–2007, Chile had the highest incidence and mortality rates in CSA (17.1 and 12.9 in females and 7.3 and 6.0 in males, respectively). Females had higher GBC rates than males. The most frequently diagnosed anatomic subsite was gallbladder (60%). Unspecified subsite represented 21% of all cases. Trends in incidence and mortality of GBC remained unchanged in Argentina, Brazil, Chile and Costa Rica in 1998–2008. Conclusion: GBC rates varied extensively across the CSA region reflecting, in part, differences in data quality, coverage and healthcare access. Chile had the highest GBC rates in CSA and the world. The large proportion of unspecified cases indicates low precision in diagnosis/registration and highlights the need to promote and improve cancer registration in the region to better understand the burden of GBC in CSA.